Exploring dog antler chews as a novel source of collagen supplementation: extraction and characterization of collagen from red deer antlers - Kamila Pepłowska; Joanna Wałecka; Paweł Bąkowski; Zbyszko Dzięgielewski; Damian Dzięgielewski; Kamilla Grzywacz (BioTechnologia, 2023)
Collagen is the body’s most abundant protein and is primarily found in the skin, bones, tendons, and ligaments of animals and fish. As the interest in collagen supplementation grows, new sources of this protein are continually being introduced. We have confirmed that red deer antlers are a source of type I collagen. We investigated the effects of chemical treatment, temperature, and time on the extractability of collagen from red deer antlers. The optimal conditions for obtaining the highest collagen yield were determined to be: 1) removing noncollagenous proteins at 25̊C for 12 h in an alkaline solution, 2) defatting at 25̊C using a 1:10 grounded antler:butyl alcohol ratio, and 3) acidic extraction lasting 36 h using a 1:10 antler:acetic acid ratio. Under these conditions, we obtained a collagen yield of 22.04%. The molecular characterization of red deer antler collagen revealed typical features of type I collagens, including the presence of three α-chains, high glycine content, and high levels of proline and hydroxyproline, as well as helical arrangements. This report suggests that red deer antlers have significant potential as a source of collagen supplements.